Hospitals and borders : seven case studies on cross-border collaboration and health system interactions - Glinos, Irene A; Wismar, Matthias (World Health Organization, 2013)
The European Union (EU) Directive on the application of patients’ rights in cross-border health care explicitly calls for Member States to cooperate in cross-border health care provision in border regions. Given that most such collaboration in the health care field involves secondary care, the new legal requirement means that hospitals that are close to national frontiers will be the focus of significant attention. But how do hospitals interact with each other and with other health care actors across borders? Why does cross-border collaboration take place? Who actually benefits from it? And when does it work? These are the questions at the heart of the present volume. Seven case studies examine the circumstances under which cross-border collaboration is likely to work, the motivations and incentives of health care actors and the role played by health systems, individuals and the EU in shaping cross-border collaboration. The study is original in offering qualitative and analytical scientific evidence on aspects of cross-border collaboration involving hospitals in 11 EU and non-EU countries (Austria, Belgium, Bulgaria, Denmark, Finland, France, Germany, the Netherlands, Norway, Romania and Spain). This book is of interest to decision-makers and field actors engaged in or considering cross-border collaboration. Questions on feasibility, desirability and implementation are at the core of the analysis. The book puts forward policy conclusions directly linked to the EU Directive on patients’ rights and proposes a “toolbox” of prerequisites for starting or maintaining cross-border collaboration in health care. In addition to its deliberate policy perspective, it also focuses on at the intersection between the EU and domestic health systems known as cross-border health care.
Observatory studies series ; 31
Keywords: Hospitals; mezinárodní spolupráce; zdravotní politika; poskytování zdravotní péče; management, organizace a řízení zdravotnictví; Health Policy; nemocnice; International Cooperation; Delivery of Health Care; veřejné zdravotnictví